2015
DOI: 10.5056/jnm15080
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review With Meta-analysis: Prompt Endoscopy As the Initial Management Strategy for Uninvestigated Dyspepsia in Asi(Aliment Pharmacol Ther 2015;41:239-252)

Abstract: SummaryDyspepsia is a common gastrointestinal (GI) symptom with 10-20% of the population in the Asia-Pacific region. Asian patients with uninvestigated dyspepsia, the diagnostic value of alarm features and the appropriateness of prompt endoscopy are remained uncertainly. Chen et al 5 performed a systematic review to evaluate the detection rate of organic diseases including upper GI malignancies and then to propose the proper initial diagnostic strategy in Asian dyspepsia patients. Among 2410 possible reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Finally, a few studies have shown that age might play an important role in the diagnosis of CSFs[ 24 , 25 ]. A previous study concluded that the presence of any warning feature and age ≥ 55 were associated with a higher risk of CSFs[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a few studies have shown that age might play an important role in the diagnosis of CSFs[ 24 , 25 ]. A previous study concluded that the presence of any warning feature and age ≥ 55 were associated with a higher risk of CSFs[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dyspepsia is a common gastrointestinal problem with over 80% of the population is affected by dyspepsia at some time in their life [1].The prevalence of dyspepsia is 10-20% in the Asia -Pacific region [2] while in the Western population range from 19 up to 41 % [3,4,5]. Dyspepsia poses a diagnostic and therapeutic challenge to the clinician [6] ,because dyspepsia is not a diagnosis, but merely a cluster of relapsing and remitting symptoms [3,7] with numerous underlying causes [8] believed to be referable to the upper gasrointestinal tract [3], thus the problem and its management remains a considerable socio-economic burden [2,3,7,9,10],although only 20 -25% of persons with dyspepsia seek medical care ,the problem is responsible for 2-5 % of visit to primary care physicians [5,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Dyspepsia is a common gastrointestinal problem with over 80% of the population is affected by dyspepsia at some time in their life [1].The prevalence of dyspepsia is 10-20% in the Asia -Pacific region [2] while in the Western population range from 19 up to 41 % [3,4,5]. Dyspepsia poses a diagnostic and therapeutic challenge to the clinician [6] ,because dyspepsia is not a diagnosis, but merely a cluster of relapsing and remitting symptoms [3,7] with numerous underlying causes [8] believed to be referable to the upper gasrointestinal tract [3], thus the problem and its management remains a considerable socio-economic burden [2,3,7,9,10],although only 20 -25% of persons with dyspepsia seek medical care ,the problem is responsible for 2-5 % of visit to primary care physicians [5,[11][12][13][14]. Because of the non-specific nature of the symptoms [9],the definitions of dyspepsia have evolved considerably over the last decades [15] and dyspepsia subclassifications ,based on dominant symptoms , are of limited value in predicting the presence and nature of clinically significant upper gastrointestinal findings in adult dyspeptic patients [12] and the current standard for the diagnosis is Rome III criteria [9,16],symptoms must be chronic, occuring for three months within the initial 6 months of symptoms onset [9]and the patient must have one or more of the following 3 symptoms: sensation of pain or burning in the epigastrium, early satiety (inability to finish a normal sized meal),fullness during or after a meal [16].…”
Section: Introductionmentioning
confidence: 99%